Immediate and late outcomes of transcatheter aortic valve implantation versus surgical aortic valve replacement in bicuspid valves: Meta‐analysis of reconstructed time‐to‐event data. Issue 10 (16th August 2022) - Sá, Michel Pompeu; Jacquemyn, Xander; Tasoudis, Panagiotis T.; Van den Eynde, Jef; Erten, Ozgun; Dokollari, Aleksander; Torregrossa, Gianluca; Sicouri, Serge; Weymann, Alexander; Ruhparwar, Arjang; Athanasiou, Thanos; Ramlawi, Basel
Abstract: Background: Outcomes of transcatheter aortic valve implantation (TAVI) versus surgical aortic valve replacement (SAVR) in patients with aortic stenosis and bicuspid aortic valve (BAV) must be better investigated. Methods: A meta‐analysis including studies published by January 2022 reporting immediate outcomes (in‐hospital death, stroke, acute kidney injury [AKI], major bleeding, new permanent pacemaker implantation [PPI], paravalvular leakage [PVL]), mortality in the follow‐up (with Kaplan–Meier curves for reconstruction of individual patient data). Results: Five studies met our eligibility criteria. No statistically significant difference was observed for in‐hospital death, stroke, AKI, and PVL. TAVI was associated with lower risk of major bleeding (odds ratio [OR]: 0.29; 95% confidence interval [CI]: 0.12–0.69; p  = .025), but higher risk of PPI (OR: 2.00; 95% CI: 1.05–3.77; p  = .041). In the follow‐up, mortality after TAVI was significantly higher in the analysis with the largest samples (HR: 1.24, 95% CI: 1.01–1.53, p  = .043), but no statistically significant difference was observed with risk‐adjusted populations (HR: 1.06, 95% CI: 0.86–1.32, p  = .57). Landmark analyses suggested a time‐varying risk with TAVI after 10 and 13 months in both largest and risk‐adjusted populations (HR: 2.13, 95% CI: 1.45–3.12, p  < .001; HR: 1.7, 95% CI: 1.11–2.61, p  = .015, respectively). Conclusion: Considering the immediate outcomes and comparable overall survival observed in risk‐adjusted populations, TAVI can be used safely in selected BAV patients. However, a time‐varying risk is present (favoring SAVR over TAVI at a later timepoint). This finding was likely driven by higher rates of PPI with TAVI.